P120 Evaluating the use of the NEWS2 SpO2 Scales in COPD patients admitted to medical wards: a prospective clinical audit. (11th November 2022) - Asfour, H; Saeed, S; Murad, A; Farman, F; Hassan, A; Punjabi, M; Jayalekshmi, S; Imdhad, R; Alkhayyer, A; Lwin, H; Sallam, A; Singh, R
Abstract : Objective: NEWS2 (RCP 2017) 1 recommends use of 'SpO2 Scale 2' in patients with hypercapnic respiratory failure (usually due to COPD) to aim target saturations of 88–92%. We aimed to identify if COPD patients admitted to medical wards have the correct NEWS2 SpO2 Scale implemented. Methods: Prospective audit of adult inpatients with COPD admitted to medical wards between (May -June 2022) at Leicester Royal Infirmary. Cases were identified through Nervecentre, an electronic patient system. Outcome measures included: evidence of ABG or VBG being performed; correct use of NEWS2 Scale 1; correct use of NEWS2 Scale 2. Results: 53 patients' data were collected, consisting of 58% male and 42% female patients. Ages ranged from 47 -96 (mean age 76). During their admission, 11% had an ABG performed, 62% had VBG performed, 6% had both ABG and VBG, and 9% had neither ABG nor VBG. In terms of NEWS2 Scale use, 75% of patients were placed on Scale 1, of which 28% were inappropriately put on this scale. 25% of patients were placed on Scale 2, of which 31% were inappropriately put on this scale. Overall, 30.2% of audited patients were placed on the incorrect NEWS2 SpO2 Scale. Conclusion: Our audit showed that nearly a third of COPD patients did not have the correct NEWS2 Scale utilised. Very few patients had an ABG performed, which would be the gold standard for identifying a need for Scale 2 usage. Careful consideration should be given when selecting the appropriate NEWS2 SpO2 Scale in COPD patients, which should be guided by evidence of hypercapnic respiratory failure. This would be important in avoiding inappropriate target saturations and O2 administration, as well as inaccurate 'scoring' of the early warning score, which can influence clinical decision-making. Recommendations include: education and awareness of correct use of NEWS2 Scales; informational posters to guide clinicians; appropriate use of ABG to identify patients suitable for Scale 2. We aim to re-evaluate after these interventions. References: Royal College of Physicians. (2017). National Early Warning Score (NEWS) 2. https://www.rcplondon.ac.uk/projects/outputs/national-early-warning-score-news-2.